If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -7) + 7 = 6x + 2 Reorder the terms: 6(-7 + x) + 7 = 6x + 2 (-7 * 6 + x * 6) + 7 = 6x + 2 (-42 + 6x) + 7 = 6x + 2 Reorder the terms: -42 + 7 + 6x = 6x + 2 Combine like terms: -42 + 7 = -35 -35 + 6x = 6x + 2 Reorder the terms: -35 + 6x = 2 + 6x Add '-6x' to each side of the equation. -35 + 6x + -6x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -35 + 0 = 2 + 6x + -6x -35 = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -35 = 2 + 0 -35 = 2 Solving -35 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(x/3+4)=12 | | 6x-7+7=6x+2 | | -5x+605=0 | | 5x+7=2(2x+5) | | 2x+4/3=12 | | 2z+3/3+3z-4=z-2/2 | | 4(-x+3)=-2(2x-6) | | 11=5(x-4)-(x-7) | | X=4(x+3)-6 | | b-1+7b=28 | | k/10=100 | | 0.1(x+60)-0.04(x-50)=5 | | 6(6x+7)=6 | | 24-2y=8y-7 | | -6a+24= | | 5+3=-4x+47 | | 6=6/10 | | 7y+12=3y-4 | | -4/3u-6=7/3u+8 | | -(4x-4)-(3x-5)+4=-9(x-1)-(2x+7)+3 | | -x-18= | | x+5-11=-3 | | (2v+9)(8-v)=0 | | 4x^3y+12x^2y-8xy= | | -(4x-4)-(3x-5)+5=-9(x-1)-(2x+7)+3 | | 6v+10=9v+9 | | 1+2x-x^2=0 | | 0.1(3.2+2x)+1/2(3-x/5)=0 | | 8x^3+18x^2-10x= | | X/31=17 | | -1.5-6x=26.7 | | 9/6=11/8 |